Azithromycin and the Outcome of Treated COVID-19 Patients: A Hospital-Based Study - Elly Usman (Universitas Andalas, 2022)
COVID-19 is an infectious disease that has been declared a pandemic. Currently, there is no validated pharmacological treatment for use in COVID-19 disease and is still in the clinical trial stage. The aim of this study to determine the association of azithromycin and the outcome of treated COVID-19 patients. This study used a retrospective cohort. The number of samples in this study were 40 subjects in each group of azithromycin and non-azithromycin. The research sample was all COVID-19 patients who were treated at Dr. M Djamil Hospital Padang with moderate and severe grades receiving treatment with azithromycin and non-azithromycin. The inclusion criteria in this study were moderate and severe COVID-19 patients and data related to research variables were complete and well-documented. Sampling technique with convenience sampling. Data analysis was performed using the Chi-square test. P < 0.05 was significant, and the data were analyzed using the SPSS version 21.0 program. The mortality of COVID-19 patients in patients receiving azithromycin therapy (80.0%) compared to non-azithromycin (85.0%). The results of the statistical test showed that there was no relationship of azithromycin administration with the outcome of COVID-19 patients (p>0.05), with OR (0.71, 95% CI 0.22-2.26). In this study, it is hoped that the decision on the use of azithromycin should consider the potential benefits and risks, evaluated that the possibility of the drug being effective is greater than the risk to the patient.